Data from: Philopatry influences the genetic population structure of the blacktip shark (Carcharhinus limbatus) at multiple spatial scales - Swift, Dominic; O'Leary, Shannon; Grubbs, Dean; Frazier, Bryan; Fields, Andrew; Gardiner, Jayne; Drymon, Marcus; Bethea, Dana; Wiley, Tonya; Portnoy, David (Zenodo, 2023)
Understanding how interactions among microevolutionary forces generate genetic population structure of exploited species is vital to the implementation of management policies that facilitate population persistence. Philopatry displayed by many coastal shark species can impact gene flow and facilitate selection, and thus has direct implications for the spatial scales of management plans. Here, genetic structure of the blacktip shark (Carcharhinus limbatus) was examined using a mixed-marker approach based on mitochondrial control region sequences and 4,339 SNP-containing loci generated using ddRAD-Seq. Genetic variation was assessed among young-of-the-year sampled in 11 sites in waters of the United States in the western North Atlantic Ocean, including the Gulf of Mexico. Spatial and environmental analyses detected 68 nuclear loci putatively under selection, enabling separate assessments of neutral and adaptive genetic structure. Both mitochondrial and neutral SNP data indicated three genetically distinct units – the Atlantic, eastern Gulf, and western Gulf – that align with regional stocks and suggest regional philopatry by males and females. Heterogeneity at loci putatively under selection, associated with temperature and salinity, was observed among sites within Gulf units, suggesting local adaptation. Furthermore, five pairs of siblings were identified in the same site across timescales corresponding with female reproductive cycles. This indicates that females re-used a site for parturition, which has the potential to facilitate the sorting of adaptive variation among neighboring sites. The results demonstrate differential impacts of microevolutionary forces at varying spatial scales and highlight the importance of conserving essential habitats to maintain sources of adaptive variation that may buffer species against environmental change. The MiSeq reference, `dDocent` config files, `genepop` file, and strata data can be opened and viewed in a text editor. The `.arp` and `.ars` files can also be opened and ...